(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
Bangladesh is a land of mighty rivers and innumerable tributaries, heavy rainfall and recurring floods. Nearly 75 percent of the country’s population depends either directly or indirectly on agriculture. This study deals with the quality of surface and ground water used in rice cultivation of Khulna district, which is located in the south-western part of Bangladesh. This study was carried out to characterize the surface and ground water in terms of different dissolved elements in relation to the suitability of the water for irrigation purposes in Khulna. To analyze the water quality for irrigation of Boro rice, the water samples both surface and ground water were collected from different Upazillas. A reconnaissance survey was conducted in different areas of sampling sites. Collected samples were immediately analyzed for finding important chemical parameters such as pH, Electrical Conductivity (EC),Sodium Adsorption Ratio (SAR), Magnesium Adsorption Ratio (MAR), Soluble Sodium Percentage (SSP),Sodium to Calcium Activity Ratio (SCAR), Sodium Ratio (SR), Residual Sodium Bi-carbonate (RSBC), Kelly’s Ratio (KR), Permeability Index (PI) and Total Hardness (HT). From the analysis, it was observed the ionic concentration and other chemical parameters varied in different water sources of the area. SAR, SSP, SCAR and KR are high in all sources where surface water contained most but SR, MAR, HT and Permeability were in favorable concentration in both sources in Khulna District. Therefore, the sodicity and alkalinity hazards risk have been found to both of the water sources to use in irrigation purposes. Bangladesh J. Sci. Ind. Res.54(3), 263-274, 2019